Credit Rating in the Islamic System: A Case Study of Saudi Arabian Banks - Hajed A. Alotaibi (Türkiye İslam İktisadı Dergisi)
Purpose: Understanding the credit agencies allows the country to diversify its investments and efficiently achieve the set goals. Therefore, the present study aimed to explore the credit rating agencies within the Saudi Islamic system. Methodology: The study employed a qualitative research design by recruiting 25 key managers working in selected Saudi banks. The data for this study has been collected through a semi-structured interview. Findings: The study results showed that the Islamic banking credit rating agency positively affects foreign business investors compared to domestic investors. The results also indicated that transparency leads to better share activisms to improve its evaluation method through better deployment. The two critical factors affecting the credit rating include the bank board’s size and its independence. Conclusion: The study has concluded that the credit rating system of any financial institution should be designed to locate the problems occurring within the Islamic banks.Originality: The study has highlighted that independent directors favor the rating system due to the achievement of better and higher rates.